Correlations between physiological variables and performance in high level cross country off road cyclists - Impellizzeri, F. M.; Marcora, S. M.; Rampinini, E.; Mognoni, P.; Sassi, A. (British Journal of Sports Medicine, 2005)
Objectives: To examine the relations between maximal and submaximal indices of aerobic fitness and off road cycling performance in a homogeneous group of high level mountain bikers.